Pertumbuhan Eksplan Pisang Cavendish Tahap Subkultur dengan Penambahan Bahan Organik pada Media Murashige and Skoog - Muhammad Radif Ashabi; Sutini; Widiwurjani (Jurnal Galung Tropika, 2024)
The productivity of cavendish bananas needs to be increased to meet the large export demand. Tissue culture techniques can produce large quantities of good-quality seedlings. This technique can use organic materials such as coconut water and bean sprout extract, which are easy to obtain at a relatively low price. This study aims to determine the effect of using coconut water and bean sprout extract on the growth of cavendish banana explants in vitro. This experiment was prepared using a completely random design (CRD) consisting of 12 treatments, namely coconut water and bean sprout extract, with concentrations of 7.5%, 10%, 12.5%, 15%, 17.5%, and 20%, respectively. The results showed that the use of coconut water was better than bean sprout extract. Treatment with coconut water at a concentration of 7.5% had the highest average value on the parameters of plantlet length. At a concentration of 12.5%, it had the highest average value on the plantlet length parameter. Meanwhile, in the concentration of coconut water, coconut water has the best concentration of 20% in the number of roots.